Ectoparasites of farmed clarias gariepinus in Eti-Osa local government area, Lagos state, Nigeria (2012)
The occurrence and prevalence of ectoparasites on farmed C/arias gariepinus from Eti-Osa local government area, Lagos State was investigated. A total of 110 fish specimens were procured from 5 farms in Eti-Osa local gov ernment area and examined for ectoparasite infestation. 5 out of the 110 fish specimens were infested giving a low prevalence rate of 4.5%. Two parasites namely Sanguinicola (blood fluke: Digenean i rental ode) and Nematode were isolated. There was no significant difference (P>0.05) between ectoparasite infestation in the male and female fish. There was no correlation between size of fish and ectoparasite infestation. Nematode had a higher prevalence, abundance and means intensity of 2.73%. 0.03 and 0.6 respectively than Sanguinicola with the values 1.82%, 0.02 and 0.4 for prevalence, abundance and means intensity respectively. All the ectoparasites were recovered from the gills, giving a prevalence rate of 4.5%. The low occurrence and prevalence of ectoparasites on farmed C. gariepinus from Eti-Osa local government area could be attributed to the high level of management observed in these farms. The high standard of pond and farm management attained by fish farmers in this local government area should be sustained. Also, the introduction of catfish fingerlings from the wild into the fish farms should be avoided